Analysis of functional and phylogenetic diversity of bat communities: insights from resource use in the Pantanal and Cerrado - Marcione B. de Oliveira; Luiz Flamarion B. de Oliveira; Cibele R. Bonvicino (Revista Chilena de Historia Natural)
Abstract Background Assessing the structure of communities requires analysis of multiple dimensions of biological diversity. Such approaches provide a broader understanding of the ecological and historical factors involved in the formation and maintenance of communities. Metrics such as functional and phylogenetic diversity are crucial as they unveil how communities respond to environmental changes, providing a deeper understanding of their current state and resilience. This goes beyond species richness or community composition, enabling more profound insights into their present condition and resilience. Therefore, analysis in this sense allows accessing differences in the distribution of species, considering different landscape mosaics, and allowing strategic prioritization of conservation initiatives. In this sense, we investigated whether the composition of functional and phylogenetic groups of chiropteran species differs between the Pantanal and Cerrado biomes and various habitat types. We hypothesize that communities with greater conservation integrity are more diverse than communities that suffer anthropogenic influences. Methods The surveyed communities include two areas in the Pantanal and two in the Cerrado, with one conservation unit and one that suffers anthropic influence, for each biome. We assessed the composition of bat assemblages by examining functional richness (FRic), functional uniformity (FEve), functional divergence (FDiv), and functional dispersion (FDis). Metrics that reflect phylogenetic richness and divergence were also used, such as phylogenetic diversity (PD), mean pairwise distance (MPD), and mean nearest taxon distance (MNTD). Results and discussion Overall, conservation units sustain higher levels of functional and phylogenetic diversity compared to areas with anthropic influence. In the latter, species occupy fewer ecological niches, indicating that bats can persist in degraded environments, albeit the communities support only a portion of the functional groups. Conclusion Our results showed, through analyses across multiple dimensions of functional and phylogenetic diversity, that bat populations are impacted by environmental degradation and fragmentation. Communities in more conserved areas exhibited higher functional and phylogenetic richness, indicating a greater number of occupied niches. These findings highlight the importance of exploring measures of biological diversity and their spatial scales to advance our understanding of biodiversity dynamics and optimize conservation planning for both species and communities.